A importância da Organização das Nações Unidas para a autodeterminação dos povos indígenas - Keyla Cristina Farias dos Santos (2017)
The United Nations General Assembly resolutions 1514, 1541 and 2625 expressly introduce the principle of self-determination as a peremptory norm of international law to proclaim the principle in respect of all peoples. This paper analyzes the extent of the peoples self-determination principle, aiming at the elimination of colonial situations and foreign domination for the free expression of their desirability, in order to elect the political formula through which carries the right to self-determination. The self-determination principle was born as a historical and political concept before turning into a concept of legal relevance, performing a very important role in the decolonization context and emerging on the international scene starting from the First World War. Relatively, the self-determination as a right of all peoples refers the internal dimension of the principle, having a universal calling in the sense which is addressed toward all peoples made in the State and that are connected to the national democratic process through the existence of their representative governments. The process of self determination, resulted in setting a pattern that was formalized in international law as a principle. In its first manifestation, as a structural principle of international law, this should serve to guide Member-States in developing their mutual relations. Then its relevance in the internal and international levels is to ensure the right attributed to peoples. When is combined the self-determination principle to the right of indigenous people, it can be understood as the right of a people to decide their own destiny, worship their languages and traditional ways of life in observance of ethnic and cultural diversity. Therefore, there is a causal connection between colonization and land alienation, territories and natural resources that the indigenous peoples suffered in the past and even today, have experienced a process of invisibility and exclusion almost systematically since de days of colonization, because of the arrival of the republican states in Latin America after the process of decolonization it did not cause significant change in the traditional relationship of subjection and submission that indigenous people were submitted. It was stablished, though, the absence of an international obligation of the State recognition of minorities should be interpreted as a limit to the discretion of States to international obligations of minorities protection, in particular, indigenous people, because their demands are articulated around the political autonomy and the special rights of the political representation, that enable them to manage their own interests as an effective exercise of the right of peoples self-determination.